The new frontier of diagnostics: Molecular assays and their role in infection prevention and control - Das, Sanchita (Am J Infect Control, 2017)
Recent advances in technology over the last decade have propelled the microbiology laboratory into a pivotal role in infection prevention and control. The rapid adaptation of molecular technologies to the field of clinical microbiology now greatly influences infectious disease management and significantly impacts infection control practices. This review discusses recent developments in molecular techniques in the diagnosis of infectious diseases. It describes the basic concepts of molecular assays, discusses their advantages and limitations, and characterizes currently available commercial assays with respect to cost, interpretive requirements, and clinical utility.